Pengaruh temperatur biogas dan waktu penyalaan terhadap kinerja motor bakar menggunakan sistem dual fuel pertamax-biogas - Mafruddin Mafruddin; Dwi Irawan; Renno Yoga Pratama; Edwin Dian Pratama (TURBO [Tulisan Riset Berbasis Online], 2021)
Biogas is an alternative fuel that can be used to replace fossil fuels which are non-renewable energy sources and their availability is decreasing. The use of biogas as fuel for gasoline engines can be done using a dual fuel system (Pertamax-Biogas). The combustion process in a gasoline engine with a dual fuel system is influenced by the temperature of the biogas and the ignition timing of the ignition system. The combustion process on a gasoline engine will affect the resulting performance. The purpose of this study was to determine the effect of biogas temperature and ignition timing on the performance of a motorcycle engine with a dual fuel system (Pertamax-Biogas). The method used in this study is an experimental study by testing the performance of a motorcycle engine using a dual fuel system (Pertamax-Biogas) using fuel temperature variations of 30°, 40°, and 50°C and ignition timing variations at 11°, 13° and 15° before Top Dead Center (TDC). The results of the study it can be concluded that the biogas temperature and ignition timing affect the performance of the motor. The highest power is obtained by varying the biogas temperature to 40°C and the ignition time to 15° before TDC, meanwhile the best specific fuel consumption was obtained at a biogas temperature variation of 50°C and an ignition time of 15° before TDC.Keywords: Dual fuel, biogas temperature, ignition time, motor performance.